Oxidative stress is associated with suspected non‐alcoholic fatty liver disease and all‐cause mortality in the general population. (28th June 2020) - Damba, Turtushikh; Bourgonje, Arno R.; Abdulle, Amaal E.; Pasch, Andreas; Sydor, Svenja; van den Berg, Eline H.; Gansevoort, Ron T.; Bakker, Stephan J. L.; Blokzijl, Hans; Dullaart, Robin P. F.; van Goor, Harry; Moshage, Han
Abstract: Background & Aims: Non‐alcoholic fatty liver disease (NAFLD) is characterized by excessive lipid accumulation, inflammation and an imbalanced redox homeostasis. We hypothesized that systemic free thiol levels, as a proxy of systemic oxidative stress, are associated with NAFLD. Methods: Protein‐adjusted serum free thiol concentrations were determined in participants from the Prevention of Renal and Vascular End‐Stage Disease (PREVEND) cohort study (n = 5562). Suspected NAFLD was defined by the Fatty Liver Index (FLI ≥ 60) and Hepatic Steatosis Index (HSI > 36). Results: Protein‐adjusted serum free thiols were significantly reduced in subjects with FLI ≥ 60 (n = 1651). In multivariable logistic regression analyses, protein‐adjusted serum free thiols were associated with NAFLD (FLI ≥ 60) (OR per doubling of concentration: 0.78 [95% CI 0.64‐0.96], P = .016) even when adjusted for potential confounding factors, including systolic blood pressure, diabetes, current smoking, use of alcohol and total cholesterol (OR 0.80 [95% CI 0.65‐0.99], P = .04). This association lost its significance (OR 0.94 [95% CI 0.73‐1.21], P = .65) after additional adjustment for high‐sensitive C‐reactive protein. Stratified analyses showed significantly differential associations of protein‐adjusted serum free thiol concentrations with suspected NAFLD for gender ( P < .02), hypertension ( P < .001) and hypercholesterolemia ( P < .003). Longitudinally, protein‐adjusted serum free thiols were significantly associated with the risk of all‐cause mortality in subjects with NAFLD (FLI ≥ 60) (HR 0.27 [95% CI 0.17‐0.45], P < .001). Conclusion: Protein‐adjusted serum free thiol levels are reduced and significantly associated with all‐cause mortality in subjects with suspected NAFLD. Quantification of free thiols may be a promising, minimally invasive strategy to improve detection of NAFLD and associated risk of all‐cause mortality in the general population.